GROUP DECISION SUPPORT SYSTEM FOR DETERMINING THE ELIGIBILITY OF PROVIDING HOUSING ASSISTANCE TO POOR FAMILIES - Ilham Sahputra; Mutammimul Ula (Informatika, Universitas Jenderal Soedirman, 2022)
It is very difficult to determine the eligibility of recipients of housing assistance for poor families, especially in gampongs, based on the number of gampong residents who apply. the large number of people who applied for assistance made it difficult for village officials and decision-makers to make decisions. The existence of a model analysis in the eligibility of recipients of housing assistance so that there is no subjectivity in the provision of assistance. The purpose of this research is to identify beneficiaries of housing assistance for underprivileged communities who meet the requirements using the Analytical Network Process (ANP) and Borda models. The variables used are parents' work (C1), number of parental dependents (C2), sources of income costs (C3), housing conditions (C4), status (C5) and education (C6). The results of selecting the ANP model were that Aminah got a score of 1.445, Hasanah (A2) 1.415, Baihaki (A3) 1.6148, Fakri (A4) 1.53. The recommendation from the ANP model analysis is baihaki with a value of 1.6148. while from the borda model the total values are A1:355, A2:355, A3:212, A4:381 A5:254, A6:209, with a weight value of 0.201, A2 weight: 0.201, A3 weight 0.120, A4 weight 0.216, A5 weight 0.144 and the weight of A6 0.118. The conclusion from the research results gives priority to the community for the highest value in obtaining housing assistance. this study which received priority baihaki with a value of 1.6148 for the results of the ANP model and the results of the value of the model group was A3 with a value of 0.272.